(untitled) (International journal of artificial intelligence, 2025)
Agriculture is one of the main sectors of the economy of every country, and its sustainable development directly affects food security, population well-being and economic growth. A solid legal framework is necessary for the effective organization of agricultural activities. This article discusses the legal framework for agricultural development, existing problems and ways to improve them.